2020
DOI: 10.3389/fendo.2020.547356
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Metabolic Profiles and Target-Organ Damage in Chinese Individuals With Primary Aldosteronism

Abstract: Purpose: Patients with primary aldosteronism (PA) have an increased risk of target-organ damage (TOD), but whether metabolic syndrome (MetS) is more prevalent and contributes to TOD in PA patients remains unresolved. We aimed to evaluate the associations between MetS profiles and TOD in Chinese PA individuals. Methods: Metabolic parameters and pre-clinical TOD including left ventricular hypertrophy, estimated glomerular filtration, and microalbuminuria; insulin sensitivity or resistance; and islet β-cell funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…One study did not provide data on sex ( 47 ). Nineteen studies were matched for demographic data ( 13 , 14 , 26 , 27 , 30 36 , 38 , 39 , 41 45 , 47 ). Regarding outcomes, 15 studies provided data on the prevalence of DM ( 2 , 13 , 14 , 27 29 , 31 , 32 , 34 , 35 , 37 39 , 47 , 48 ), 4 studies on IFG ( 2 , 14 , 35 , 40 ) and 5 studies on IGT ( 25 , 28 , 35 , 36 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study did not provide data on sex ( 47 ). Nineteen studies were matched for demographic data ( 13 , 14 , 26 , 27 , 30 36 , 38 , 39 , 41 45 , 47 ). Regarding outcomes, 15 studies provided data on the prevalence of DM ( 2 , 13 , 14 , 27 29 , 31 , 32 , 34 , 35 , 37 39 , 47 , 48 ), 4 studies on IFG ( 2 , 14 , 35 , 40 ) and 5 studies on IGT ( 25 , 28 , 35 , 36 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding outcomes, 15 studies provided data on the prevalence of DM ( 2 , 13 , 14 , 27 29 , 31 , 32 , 34 , 35 , 37 39 , 47 , 48 ), 4 studies on IFG ( 2 , 14 , 35 , 40 ) and 5 studies on IGT ( 25 , 28 , 35 , 36 , 47 ). Twenty studies included data on FBG ( 2 , 14 , 25 , 27 , 28 , 30 , 32 , 34 38 , 40 – 47 ) with 10 studies excluded DM patients or discontinuing hypoglycemic agents before recruitment ( 25 , 30 , 36 , 40 46 ), 7 on HbA1c ( 13 , 25 , 26 , 30 , 31 , 36 ), 5 on 2-hr OGTT ( 25 , 30 , 32 , 36 , 47 ), 10 on HOMA-IR ( 25 , 26 , 28 , 30 , 33 , 36 , 41 44 ), 5 on HOMA-ß ( 26 , 30 , 33 , 43 , 45 ), 3 on AUC of glucose ( 25 , 26 , 45 ), 4 on AUC of insulin ( 25 , 26 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study excluded patients who used statins [ 10 ]. In one study, statins were withdrawn for 4 weeks prior to lipid profile evaluation [ 47 ], while five studies stated that statins were continued during the study [ 12 , 30 , 33 , 40 , 51 ]. The remaining studies did not mention this issue.…”
Section: Resultsmentioning
confidence: 99%
“…The structural renal damage induced by a high PAC in patients with PA may be associated with unfortunate outcomes, such as renal injury and renal failure (137,138). Patients with PA presented more frequently with microalbuminuria and albuminuria, lower eGFR, and increased creatinine levels (111,136,139,140). Studies have reported that albuminuria and renal failure were found in a range from 8 to 24% in subjects with PA (138,141).…”
Section: Toxic Effects Of Aldosterone On the Kidneymentioning
confidence: 99%